THE INFLUENCE OF EDUCATION THROUGH BOOKLET MEDIA ON KNOWLEDGE ABOUT LONG TERM CONTRACEPTION METHODS IN WOMEN - Sri Sulistyowati, Anita; Prastyoningsih, Aris (Universitas Kusuma Husada Surakarta, 2025)
The long -term contraceptive method is the most effective contraceptive method for reducing birth rates but its users are only 20.3%. The National Family Planning Program prioritizes the use of Long -Term Contraception Methods, but the scope of long-term contraception is still low. This study aims to analyze the effect of education through media booklets on knowledge of long -term contraceptive methods in women of childbearing age in the village of Kajoran Klaten Selatan. The type of research is a quantitative research, with the Without Control Design pretest-post approach with the research sample is a woman of fertile age in Kajoran Village, amounting to 52 women of childbearing age. The study was conducted in May 2024. Statistic test using descriptive statistics and Wilcoxon test. The results showed that there was there an increase in the average knowledge value of respondents before and after being given education through booklets. From 73.8 to 84.3 with an increase in score of 10,5. the effect of providing education through booklets on the knowledge of women of childbearing age about the long -term contraceptive method with p value 0,000 (<0.05).